The CDC Denies Magnetic Elements in COVID Injectables While DARPA Promotes Mind-Control Research with Magnetic Nanoparticles Migrated to the Brain - Oller, Jr., John W.; Santiago, Daniel; Broudy, Daniel (International Journal of Innovative Research in Medical Science, 2025)
The CDC denies that COVID-19 injections from Pfizer, Moderna, or Novavax can cause magnetism, even at the site of the injection. The CDC claims that the three ferromagnetic metals consisting of iron, cobalt, and nickel, and the rare earth chemicals used in magnets cerium, hafnium, lanthanum, gadolinium, and erbium are not in the US approved injectables. However, a 2024 study using inductively coupled plasma-mass spectrometry (ICP-MS), detected all these and many other undeclared elements in lots of Pfizer, Moderna, and five other brands of COVID-19 injectables. By contrast with the CDC denials, James Giordano, who has become Director of the Defense Advanced Research Projects Agency (DARPA), has argued since 2018 that the human brain is the battleground for DARPA’s “disruptive technologies” of warfare using magnetic nanoparticles delivered “intranasally, intravenously, or intraorally” all without surgery to achieve “mind-control” by adjusting the frequencies, power, and directionality of the electromagnetic forces. The science of magnetofection is little known but has been under development for decades. We explain it here and ask, could militarized experimentation with magnetic nanoparticles be involved in causing the documented outcomes of proteinaceous clotting, cardio-vascular conditions, strokes, new autoimmune diseases, unprecedented rapidly developing “prion diseases”, “turbo” cancers, and sudden deaths many of these occurring in otherwise young and healthy recipients of the experimental COVID-19 injectables? The research discussed in this paper implies that an affirmative answer cannot be ruled out.